INTEGRO-DIFFERENCE EQUATION FOR A CORRELATION-FUNCTION OF THE SPIN-1/2 HEISENBERG XXZ CHAIN - Essler, F; Frahm, H; Its, A; Korepin, V (1995)
We consider the Ferromagnetic-String-Formation-Probability correlation function (FSFP) for the spin- 1 2 Heisenberg XXZ chain. We construct a, completely integrable system of integro-difference equations (IDE), which has the FSFP as a, τ-function. We derive the associated Riemann-Hilbert problem and obtain the long-distance asymptotics of the FSFP correlator in some limiting cases. © 1995.